Integrating Multidisciplinary Perspectives: An Editorial Introducing the International Journal of Culture, Tourism and Hospitality Research - Woodside, Arch; Crotts, J.; Harrill, R. (Emerald Group Publishing Ltd., 2007)
Purpose – The purpose of this editorial is to introduce the International Journal of Culture, Tourism and Hospitality Research. Design/methodology/approach – The paper outlines the primary objective of IJCTHR. Findings – The journal is designed to serve as a valuable platform for new theory and research articles that integrate multidisciplinary perspectives in describing, explaining, predicting, and influencing tourism and hospitality behavior within and across cultures. Originality/value – The editorial describes the objectives of IJCTHR and, as the principal publication for the International Society of Culture, Tourism, and Hospitality Research, invites membership to the society, which is open to all scholars and individuals with professional or personal interests in acquiring knowledge on topics relating to culture, tourism, and hospitality.